The Relationship Between Accounting Education, Professional Certification, Decision-Making Ethics on Audit Quality in 5 Manufacturing Companies in West Java - Salwa Aulia Novitasari (West Science Social and Humanities Studies, 2023)
This research study examines the relationship between accounting education, professional certification, decision-making ethics, and audit quality in the manufacturing sector. This research focuses on five manufacturing companies located in West Java, Indonesia. Its main objective is to investigate how accounting education, professional certification, and decision-making ethics affect audit quality in such firms. Quantitative research designs were used, and data were collected through structured questionnaires given to accounting and auditing professionals. The findings show a positive correlation between accounting education, professional certification, decision-making ethics, and audit quality. Further regression analysis revealed that these factors collectively predict audit quality in manufacturing firms. The study highlights the importance of continuing education, professional certification, and ethical behavior in improving audit quality. These findings contribute to the existing literature and offer valuable insights for manufacturing companies looking to improve their accounting and auditing practices.